2013
DOI: 10.1177/0269881113504016
|View full text |Cite
|
Sign up to set email alerts
|

Repeated aripiprazole treatment causes dopamine D2 receptor up-regulation and dopamine supersensitivity in young rats

Abstract: Aripiprazole is a second-generation antipsychotic that is increasingly being prescribed to children and adolescents. Despite this trend, little preclinical research has been done on the neural and behavioral actions of aripiprazole during early development. In the present study, young male and female Sprague-Dawley rats were pretreated with vehicle, haloperidol (1 mg/kg), or aripiprazole (10 mg/kg) once daily on postnatal days (PD) 10–20. After one, four, or eight days (i.e., on PD 21, PD 24, or PD 28), amphet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 90 publications
1
26
0
Order By: Relevance
“…The activity level of young rats that received daily risperidone did not differ from controls after 1, 7, or 14 days of injections (i.e., on PNDs 15, 22, and 29) when tested 23.6 hours after the last injection. This is consistent with a recent study (Varela et al, 2014) that found that haloperidol treatment between PNDs 10–20 did not modify locomotor responses to saline on PNDs 21, 24, or 28. As discussed above, elevations in D 2 receptor density may be required for compensatory hyperactivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The activity level of young rats that received daily risperidone did not differ from controls after 1, 7, or 14 days of injections (i.e., on PNDs 15, 22, and 29) when tested 23.6 hours after the last injection. This is consistent with a recent study (Varela et al, 2014) that found that haloperidol treatment between PNDs 10–20 did not modify locomotor responses to saline on PNDs 21, 24, or 28. As discussed above, elevations in D 2 receptor density may be required for compensatory hyperactivity.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies reported similar changes in adult rats after only a single APD injection, and the duration of dopaminergic supersensitivity typically mirrors the duration of drug exposure (see Muller & Seeman 1979 for review). Varela and colleagues (2014) generated comparable data in younger rats by showing that haloperidol or aripiprazole injected daily between PNDs 10–20 increased amphetamine-induced sniffing and elevated striatal D 2 densities between PNDs 21–28. Despite this work, it remains unclear as to if and when the locomotor hyperactivity produced by early-life risperidone administration (Bardgett et al, 2013) emerges during the course of administration, and if it evolves in a manner consistent with its emergence in adults (Muller & Seeman, 1979).…”
Section: Introductionmentioning
confidence: 85%
“…Conversely, the same high dose of cocaine (20 mg/kg) further enhanced the locomotor activity of adolescent and adult rats. This pattern of effects indicates that the PD 20 age group had a greater sensitivity to cocaine, because the transition from predominately nonstereotyped to stereotyped behavior occurred at a lower dose in preweanling rats than adults (for a discussion of psychostimulants and “behavioral competition,” see Morelli et al 1980; Bordi et al 1989; Varela et al 2014). Comparisons between adolescent and adult rats showed that cocaine sensitivity, at least in terms of %Hab scores, varied only slightly according to age.…”
Section: Discussionmentioning
confidence: 98%
“…Although current clinical research into the use of APDs in the adolescent population over both a short term period of between 1-2 months, and longer-term period of up to 6 months has found some benefits in the treatment of some mental illness symptomology (Stigler et al 2004; Kumra et al 2008;Zuddas et al 2011), there is limited data on the potential for longterm alterations to adult behaviours (Milstein et al 2013;Shu et al 2014;Varela et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of childhood/adolescent APD use on adult behaviours is unknown in a clinical setting, current animal studies have shown that early drug treatment for a period of up to 4 weeks can result in various significant alterations in the dopaminergic and serotonergic pathways in the brain long-term (Maciag et al 2006;Moran-Gates et al 2006;Vinish et al 2012;Milstein et al 2013;Varela et al 2014), including permanent changes in the distribution of NT receptors and dendritic architecture (Maciag et al 2006;Moran-Gates et al 2006;Milstein et al 2013), with minimal evidence of the direct effects on behaviour. Alterations to the production, transport and binding of DA and 5-HT in the cortical and striatal brain regions have already been directly linked to changes in behavioural attributes, including locomotor activity levels along with depressive-like and anxiety-like behaviours.…”
Section: Introductionmentioning
confidence: 99%